CRIMINAL LIABILITY FOR MEDICAL PERSONNEL IN BEAUTY MALPRACTICE CASES - Theodorus Patrick; Luthfillah Arrizqi Zainsyah (Ajudikasi : Jurnal Ilmu Hukum, 2025)
The purpose of this study is to analyze the basis of criminal law regulation against medical personnel as well as the form of legal protection for victims of beauty malpractice. This research is motivated by the increasing practice of medical aesthetics in Indonesia which often raises legal problems due to medical actions that are not in accordance with professional standards. The urgency of this research lies in the need to clarify the boundaries between ethical, administrative, and criminal violations in aesthetic medicine practice so that there is no excessive criminalization of medical personnel. This study uses normative legal methods with statutory approaches, conceptual approaches, and case approaches. The results of the study show that there is an overlap of norms between the Criminal Code and the Medical Practice Law in the application of the principle of lex specialis derogat legi generali, as well as the need to affirm the recommendation mechanism of the Professional Disciplinary Council as stipulated in Law Number 17 of 2023 concerning Health. The free verdict in the analyzed case was caused by the weak evidence of the culpa lata element and the judge's error in assessing the absence of written informed consent. In conclusion, the legal system needs to strengthen the integration between ethical, administrative, civil, and criminal pathways in order to create legal protection that is balanced between the rights of patients and the professional responsibilities of medical personnel. The findings or novelty of this research is the identification of the need for harmonization between general criminal law and health law in the enforcement of the criminal responsibility of doctors in the field of aesthetics